Digital pen with multi-purpose mouse functionality - Mizi, Md. Shofiqul Azad; Ahmed, Sadman; Khan, Irtiza Yamin; Islam, Md. Saiful (BRAC University, 2017)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2016.